ARTISTIC EXPRESSION OF TRAGEDY AND DECISION IN SCOTT TUROW'S NOVELS (Global Conference on Multidisciplinary Research and Innovation, 2026)
Scott Turov is considered one of the writers who made the greatest contribution to the development of American legal thriller in the late 20th and early 21st centuries. Both as a writer and as a practicing lawyer, he is a man who has deeply mastered the internal mechanisms of the legal system, creating complex dramatic scenes in his novels that revolve around the courtroom, the criminal investigation, and the moral choice of the individual. The most important feature that distinguishes Turov's creative style from representatives of other genres is that he interprets the judicial process not merely as a means of solving a mysterious crime, but as an artistic field that reveals a person's inner world, their struggle with sin and conscience, and the moral veins of society. It is for this reason that both the tragedy and the solution in his works are simultaneously both legal and existential in nature, leading the reader not only to a simple detective interest but also to deep philosophical reflection.